EFEKTIVITAS PERAWATAN MALODOR LUKA KANKER MENGGUNAKAN FORMULA TOPIKAL INOVATIF (FTI) DALAM UPAYA MENINGKATKAN KUALITAS HIDUP PASIEN KANKER PAYUDARA (Journal of Hospital Management, 2018)
Breast cancer with chronic wounds has a complex problem in wound management. One of the physical problem that can decrease the quality of life of patients with cancer wounds is an unpleasant odor arising from cancer wounds (malodor). The right treatment strategy is a main priority to improve the quality of life of the patients. This study aims to identified the difference of the average score decrease of the perception of physical response (malodor) in breast cancer wound using an innovative topical formula (ITF) compared to the standard topical formula (STF). Research design is a randomized controlled trial. The study involved 90 patients with breast cancer wounds who has come to wound care at Dharmais Wound Care Clinic in the February 2012 - June 2013 period. The out put of the study is a decrease of the average score of malodor perception by nurses and families. The results showed a decrease of the average score of malodor perception by nurses, (6.45 ± 1.37) vs (4.12 ± 1.45) p = 0.001, and a decrease of the average score of malodor perception by the family; (7.87 ± 1.41) vs (4.12 ± 1.26) p = 0.001. Variable perceptions of malodor by nurses and perceptions of malodor by family are influenced by demographic characteristics, stage of breast cancer and characteristics of cancer wounds (p <0,05). The decline in malodor score has an impact on improving the quality of life of patients with breast cancer wounds.Keywords: ITFI, malodor, breast cancer, wounds care, quality of life